Curcumin and exercise prevent depression via alleviating hippocampus injury and improve depressive-like behaviors in chronically stressed depression rats - Elaheh Ahmadi; Ali Pourmotabbed; Nilofar Aghaz; Seyed Ershad Nedaei; Mojgan Veisi; Zahra Salimi; Fatemeh Zarei; Cyrus Jalili; Farshad Moradpour; Motahareh Zeinivand (Research in Pharmaceutical Sciences)
Background and purpose: Depression is a growing public health concern worldwide, characterized by cognitive impairment and structural abnormalities of the hippocampus. Current antidepressant treatment sometimes causes the late onset of results and the much faster occurrence of side effects. For this reason, the interest in new treatment strategies including exercise and natural products such as curcumin has increased to treat depression. The present study investigated the role of curcumin and exercise in improving depressive-like behavior and hippocampal damage induced by mild unpredictable chronic stress in male rats. Experimental approach: This study analyzed the effects of curcumin (100 mg/kg/day, P.O for 14 days) and exercise (treadmill running, 45 min/day for 14 days) on immobility behavior (forced swimming test), locomotor activity (open field test), anhedonia (sucrose preference test) and cell survival (Nissl staining) of the hippocampal CA3 region in chronically stressed depression rats. Findings/Results: In the current study, curcumin treatment combined with exercise effectively improved immobility behavior, locomotor activity, and increased hippocampal cell survival resulted in preventing the development of hippocampus dysfunction and depressive-like behaviors. Conclusion and implications: This study demonstrated a new prospect for treating depression. The current findings give researchers the confidence to continue the investigations on the effects of curcumin accompanied with exercise as a novel therapy for the treatment of depression.